Financial Feasibility Study to Determine the Best Funding Structure for Garuda Project in Pt Asgardian Muda - Ineu Utami Dewi; Raden Aswin Rahadi (Eduvest - Journal of Universal Studies, 2025)
The pharmaceutical industry faces growing regulatory challenges and financial constraints when expanding into new markets. This study evaluates the financial feasibility of the Garuda Project, a strategic initiative by PT Asgardian Muda to build a pharmaceutical manufacturing facility meeting European Good Manufacturing Practices (GMP) standards. The aim is to determine the most suitable funding structure to ensure financial sustainability and regulatory compliance. The research uses both qualitative and quantitative methods, including financial performance analysis, stakeholder evaluation, and investment feasibility assessment. Key financial metrics, such as Net Present Value (NPV), Internal Rate of Return (IRR), and Weighted Average Cost of Capital (WACC), are applied to compare different funding options: internal financing, debt-based funding, and hybrid models. Sensitivity analysis also examines the impact of factors like interest rates, Cost of Goods Sold (COGS), demand fluctuations, and delayed regulatory approval on financial viability. Findings indicate that all scenarios are financially feasible, with IRRs surpassing the WACC. The 50% equity and 50% debt hybrid model performs best, offering the highest NPV (up to IDR 226 billion), a lower WACC (8.74%), and the shortest payback period (2044). Sensitivity analysis shows the project is most sensitive to regulatory approval delays and market demand fluctuations. The Garuda Project is both economically and strategically viable, with the hybrid funding model providing an optimal balance between profitability and risk. If the company adheres to its zero-debt policy, the project remains feasible under a 100% equity structure, although with reduced financial efficiency.